Effect of oxidation method of cadmium and zinc chalcogenide substrates on physical properties of CdO and ZnO heterolayers - Makhniy, V.P.; Boiko, Yu.N.; Skrypnyk, N.V.; Slyotov, M.M.; Khusnutdinov, S.V. (Functional Materials, 2009)
Formation of CdO and ZnO heterolayers on cadmium and zinc chalcogenide substrates by oxidation and effect of the formation method on physical properties of the oxides are discussed.